Global Prevalence and Drivers of Dental Students’ COVID-19 Vaccine Hesitancy - Riad, Abanoub (Vaccines (Basel), 2021)
Background: Acceleration of mass vaccination strategies is the only pathway to overcome the COVID-19 pandemic. Healthcare professionals and students have a key role in shaping public opinion about vaccines. This study aimed to evaluate the attitudes of dental students globally towards COVID-19 vaccines and explore the potential drivers for students’ acceptance levels. Methods: A global cross-sectional study was carried out in February 2021 using an online questionnaire. The study was liaised by the scientific committee of the International Association of Dental Students (IADS), and data were collected through the national and local coordinators of IADS member organizations. The dependent variable was the willingness to take the COVID-19 vaccine, and the independent variables included demographic characteristics, COVID-19-related experience, and the drivers of COVID-19 vaccine-related attitude suggested by the WHO SAGE. Results: A total of 6639 students from 22 countries, representing all world regions, responded to the questionnaire properly. Their mean age was 22.1 ± 2.8 (17–40) years, and the majority were females (70.5%), in clinical years (66.8%), and from upper-middle-income economies (45.7%). In general, 22.5% of dental students worldwide were hesitant, and 13.9% rejected COVID-19 vaccines. The students in low- and lower-middle-income (LLMI) economies had significantly higher levels of vaccine hesitancy compared to their peers in upper-middle- and high-income (UMHI) economies (30.4% vs. 19.8%; p < 0.01). Conclusions: The global acceptance level of dental students for COVID-19 vaccines was suboptimal, and their worrisome level of vaccine hesitancy was influenced by the socioeconomic context where the dental students live and study. The media and social media, public figures, insufficient knowledge about vaccines, and mistrust of governments and the pharmaceutical industry were barriers to vaccination. The findings of this study call for further implementation of epidemiology (infectious diseases) education within undergraduate dental curricula.